Heat stress investigation on laundry workers - Md Jalil, Mohd Azlis Sani (2007)
Heat stress is one of the occupational hazards in hot working environment. Hot conditions will put the body under a lot of stress. This paper will discuss the results on investigation of heat stress among employees at the selected Dr. Clean laundries around Johor Bahru, Johor. In this study, heat stress level was determined based on Wet Bulb Globe Temperature Index (WBGT) and Heat Stress Index (HSI). It was found that level of heat stress as defined by WBGT at one of the laundries (Dr. Clean Surplus Prisma Sdn Bhd, Bandar Baru Uda) had slightly exceeded Threshold Limit Value (TLV) limit as 28.78OC; more than 28OC and 28.5OC as recommended by the ISO 7243 Standard and ACGIH Standard respectively. Whereas, Laundry 2 (Dr Clean Ambang Elit Sdn Bhd, Bandar Putra Kulai) and 3 (Dr Clean Prisma Ilusi Sdn Bhd, Taman Mutiara Rini) were recorded as 26.41 and 27.04 respectively. However, the Heat Stress Index of Belding and Hatch (HSI) value shows possibility of mild to moderate heat strain may occur at all outlets. HSI index for Laundry 1, 2 and 3 were exceeded range of 0-10 recommended by ISO 7243 as 28.45, 26.81 and 26.01 respectively. In conclusion, Dr Clean outlets in Johor could be considered as hot working environment since heat stress was determined among laundry workers; but in a very initial stage.